Elevated IL18 levels in Nasopharyngeal carcinoma induced PD-1 expression on NK cells in TILS leading to poor prognosis. (May 2020) - Liou, Anthony Kian-Fong; Soon, Gwyneth; Tan, Louise; Peng, Yang; Cher, Boon Meng; Goh, Boon Cher; Wang, Shi; Lim, Chwee Ming
Highlights: Tumor infiltrating NK cells has a bimodal distribution in NPC with prognostic significance. Patients with high levels of tumour infiltrating NK cells (NK high ) have a worse prognosis. Higher percentage of NK cells in NK high cohort expressed PD-1. IL-18 alone within the tumor microenvironment induces PD-1 expression on NK cells in a dose-dependent manner. Abstract: Objectives: Characterisation of tumor-infiltrating lymphocytes (TILS) population for cancer prognostication has enabled deeper understanding of tumor immune interactions in cancer immunology. We aim to examine the significance of both the density and functional status of NK cells in a cohort of Epstein Barr Virus (EBV) associated Nasopharyngeal Cancer (NPC) patients. Methods: NK TILS of 50 NPC samples were quantified on immunohistochemistry and the density of NK TILS was correlated with clinical outcomes. Next, NK cells and a panel of cytokines of 10 newly diagnosed NPC patients were characterized in both NPC tissue and peripheral circulation. Exhausted NK cells were identified using co-expression of PD-1 and/or Tim-3. Comparison of percentage of NK cells in NPC and healthy controls was performed using student t -test for two groups; and a p value of less than 0.05 values was considered significant. Results: NK TILS exhibited a bimodal distribution; with the NK high cohort demonstrating a poorer 2-year overall survival rate (p < 0.035). In-vitro studies revealed a higher proportion of infiltrated NK cells in the NK high cohort co-expressed PD-1. Additionally, IL-18 levels in NPC tissue were significantly higher than in healthy nasopharynx; and IL-18 alone induced PD-1 expression on NK cells. Expectedly, plasma IL-18 concentration and percentage of circulating PD-1-expressing NK cells were similar among NPC patients and healthy controls. Conclusion: The cytotoxic function of NK TILS is mitigated by an elevated IL-18 levels within the NPC microenvironment. Hence, the functional status, and the density of NK cells in TILS should be considered when prognosticating NPC.